Incidence of thyroid dysfunction in children after HSCT with reduced intensity conditioning (RIC) or myeloablative conditioning (MAC). (6th February 2021) - Wang, YunZu M.; Howell, Jonathan C.; Grimley, Michael S.; Lane, Adam; Davies, Stella M.; Myers, Kasiani C.
Abstract: We have previously demonstrated a 11% incidence of post‐transplant de novo thyroid disease, even with a radiation‐free RIC regimen. Following the enactment of a universal late effects screening program at our institution, we compared the outcomes of 108 pediatric hematopoietic stem cell transplant recipients after a RIC regimen ( n  = 33) to those after a MAC regimen ( n  = 75) during the same time period. Overall, 10% of subjects developed thyroid dysfunction after HSCT, with a median follow‐up of 669 days. Seven subjects had primary hypothyroidism prior to HSCT. Of the thirty‐one subjects who received RIC, one (3.2%) developed a new thyroid disorder, compared to the nine of sixty‐nine (13.0%) subjects who received MAC ( p  = .167). No significant associations were seen with donor type, graft‐vs.‐host disease, or total body irradiation. Nine of the 10 subjects who developed thyroid disease after transplant were asymptomatic. Continued follow‐up of this contemporary cohort will further delineate risk factors for post‐transplant‐associated thyroid dysfunction and better inform discussions of transplant‐associated sequelae.